2010
DOI: 10.1016/j.tsf.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Thin polymerized C60 coatings deposited in electrostatic field via electron-beam dispersion of fullerite

Abstract: The aim of the present study is to clarify the charge composition of fullerite C 60 electron-beam dispersion (EBD) products and investigate the influence of fullerene ions and electrons on the structure of the deposited coatings by applying an additional electrostatic field to the substrates. It was found that C 60 EBD products contain positive fullerene ions and electrons. By using Raman and attenuated total reflection Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, laser desorption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Hence, the ionization of C 60 vapor is facilitated inside the microcavities as compared to the direct sublimation from the surface. Indeed, we have previously shown that during the quasi-stationary deposition, the products of fullerite C 60 EBD contain few mass percent of positive fullerene ions with the energy of up to ≈ 7 eV [13] that strongly influence the coating structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the ionization of C 60 vapor is facilitated inside the microcavities as compared to the direct sublimation from the surface. Indeed, we have previously shown that during the quasi-stationary deposition, the products of fullerite C 60 EBD contain few mass percent of positive fullerene ions with the energy of up to ≈ 7 eV [13] that strongly influence the coating structure.…”
Section: Resultsmentioning
confidence: 99%
“…The effective mass thickness of the coating deposited on the substrate was monitored by a quartz crystal microbalance (QCM). To recalculate the obtained data into the geometrical thickness, the mass density of the deposited material was chosen to be equal to the mass density of fullerite C 60 (1720 kg/m 3 ) as no micro-size pores or defects were found in the deposited films using the atomic-force microscopy measurement [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homopolymers contain fullerene moieties linked to one another via [2+2] cycloaddition to form a polymeric network. This cycloaddition is induced by excitation with photons, [47,[115][116][117] electrons, [48,[118][119][120] plasma discharge, [121] or the application of a high hydrostatic pressure. [50,[122][123][124] Fullerene homopolymers have also been observed in the ambient temperature phases of alkali metal fullerides.…”
Section: Fullerene Homopolymersmentioning
confidence: 99%
“…Reproduced with permission. [118] Copyright 2010, Elsevier. In the bird's-eye view, one stacking fault is introduced as a BCBC stacking that can be identified to be HCP-m. Reproduced with permission.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%